5 Elemen Dalam Pemahaman Bahasa Plato - Lukita, Ardina; Charis, Jessica (CV. ITTC INDONESIA, 2023)
This research aims to explore key elements in Plato's theory of language understanding, discussing philosophical implications for understand language, language systems and words. The analysis carried out to further insight about how understand language in complex interactions in contemporary society which is constantly changing. This inquiry views 5 main elements of understanding language proposed by Plato, thats: The function of language description to describe objects; Etymology/origins of words; A vocal portrait of the essential nature of the object, the dual function of language as instruction and separating the existence of culture; and Elements of language conventions as an arbitrary system agreed upon by its speakers. Giving a 'name' to an object or situation provides meaning in understanding the world. The philosophical value of words is basically a means of communication, interpersonal and intrapersonal, verbal or written. With this, Plato provided the foundation for philosophical thought to achieve true knowledge, which now makes a major contribution to the development of various scientific disciplines.